Intergovernmental Transfers and Pareto Optimality - David Allan Vardy (Queen's University, Department of Economics, 1972)
This paper will examine a variety of models in which the affected governments modify their behavior in response to spillover benefits. Initiallly, governments will adjust to the 'income effects' of benefit spill-ins, but it will be shown that intergovernmental compensation will generally be required in order to achieve Pareto optimality.
Keywords: 330